2017
DOI: 10.1111/ffe.12622
|View full text |Cite
|
Sign up to set email alerts
|

Fracture mechanical characterization of the initiation and growth of interior fatigue cracks

Abstract: The formation and growth of interior fatigue cracks have been studied thoroughly during the last decades, due to the high practical importance of accurate predictions about the fatigue lives of structures and machine components. This is of special interest in the VHCF regime, for which the ultrasonic fatigue method is especially useful. Fracture mechanical values and lifetimes can be measured at constant and variable amplitudes. Endurance limits and ΔK thresholds can also be determined very quickly (e.g. 1010 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…Knowing the effect of environment on the VHCF strength is also very important to better understand internal crack initiation . It is well known that crack growth rate is greater in humid air than in vacuum . This is in agreement with the observation of a very long incubation period for crack initiation which is characteristic of the gigacycle regime.…”
Section: Effect Of Microstructural and Mechanical Features On The Vhcsupporting
confidence: 59%
See 1 more Smart Citation
“…Knowing the effect of environment on the VHCF strength is also very important to better understand internal crack initiation . It is well known that crack growth rate is greater in humid air than in vacuum . This is in agreement with the observation of a very long incubation period for crack initiation which is characteristic of the gigacycle regime.…”
Section: Effect Of Microstructural and Mechanical Features On The Vhcsupporting
confidence: 59%
“…Very recently, Stanzl‐Tschegg showed that on “Type I” material (high‐purity copper), internal fatigue crack initiation can be observed in the VHCF regime, but 10 10 cycles were needed to observe that. The reason of such initiation is still unknown even if short cracks (20 μm long) seem to play the role of newly existing defects.…”
Section: From High Cycle Fatigue (Hcf) To Very High Cycle Fatigue (Vhmentioning
confidence: 99%
“…In practice, the interior fatigue cracks predominantly can be formed at a very high number of cycles. The formation and the growth of interior fatigue cracks depend on numerous factors, such as a composition of materials, microstructure, and surface condition as well as various loading parameters and the environment . Correspondingly, Sandaiji et al conducted the torsional fatigue tests in the VHCF regime, and they showed the different internal fatigue crack behaviors associated with the different types of inclusion for the shot‐peened specimens.…”
Section: Resultsmentioning
confidence: 99%
“…It occurs under stress lower than the 10 7 lifetime defined fatigue strength. It was revealed that smaller defects with length up to 40 μm could cause VHCF failure …”
Section: Resultsmentioning
confidence: 99%